Effects of Low Temperature Storage on the Quality and Volatile Components of Indica-japonica Hybrid Rice with Different Forms - RANG Xue-na; DONG Yi-fei; ZHU Lin (Liang you shipin ke-ji, 2024)
To elucidate the variations in quality and volatile component changes in different forms of stored indica-japonica hybrid rice, a study was conducted with Yongyou 1540 rice as the test material. Under storage conditions of paddy, brown rice, and milled rice, compared to conventional warehousing, an investigation was conducted to assess the influence of low-temperature storage (15±1 ℃, RH 60%) on its quality (fatty acid value, sensory evaluation) and volatile components. Results showed that storing rice at low temperatures significantly enhanced sensory quality when comparing with conventional storage after six months, and the fatty acid value was notably superior after 12 months. Moreover, storing rice as paddy or brown rice significantly outperformed milled rice storage (at 12 months). Analysis using gas chromatography-ion mobility spectrometry (GC-IMS) to examine the volatile components of the rice under different treatments, aldehyde and ketone substances in rice stored for 6~12 months increased in comparison of fresh rice. Among these, the differences in volatile components were relatively minor between samples stored for 6 months and notably greater between samples stored for 12 months. Substances like 2-methyl-1-butanol, pentanal, hexanal, 3-methylbutanal were found in higher concentrations in room temperature samples compared to low-temperature storage, while cyclohexanone, 2-butanone, butanal, 3-hydroxy-2-butanone were lower in concentration. In conclusion, low-temperature storage of paddy or brown rice maintained the quality and volatile components of indica-japonica hybrid rice better than those of conventional storage. This research can provide essential data and theoretical foundations for post-harvest storage and production of indica-japonica hybrid rice.